Nurse's Achilles Heel: Using Big Data to Determine Workload Factors That Impact Near Misses. Issue 3 (30th March 2021) - Campbell, Amy A.; Harlan, Todd; Campbell, Matt; Mulekar, Madhuri S.; Wang, Bin
Abstract: Purpose: To explore how big data can be used to identify the contribution or influence of six specific workload variables: patient count, medication count, task count call lights, patient sepsis score, and hours worked on the occurrence of a near miss (NM) by individual nurses. Design: A correlational and cross‐section research design was used to collect over 82, 000 useable data points of historical workload data from the three unique systems on a medical‐surgical unit in a midsized hospital in the southeast United States over a 60‐day period. Data were collected prior to the start of the Covid‐19 pandemic in the United States. Methods: Combined data were analyzed using JMP Pro version 12. Mean responses from two groups were compared using a t‐test and those from more than two groups using analysis of variance. Logistic regression was used to determine the significance of impact each workload variable had on individual nurses' ability to administer medications successfully as measured by occurrence of NMs. Findings: The mean outcome of each of the six workload factors measured differed significantly ( p < .0001) among nurses. The mean outcome for all workload factors except the hours worked was found to be significantly higher ( p < .0001) for those who committed an NM compared to those who did not. At least one workload variable was observed to be significantly associated ( p < .05) with the occurrence or nonoccurrence of NMs in 82.6% of the nurses in the study. Conclusions: For the majority of the nurses in our study, the occurrence of an NM was significantly impacted by at least one workload variable. Because the specific variables that impact performance are different for each individual nurse, decreasing only one variable, such as patient load, will not adequately address the risk for NMs. Other variables not studied here, such as education and experience, might be associated with the occurrence of NMs. Clinical Relevance: In the majority of nurses, different workload variables increase their risk for an NM, suggesting that interventions addressing medication errors should be implemented based on the individual's risk profile.